Environmentally acquired chemical camouflage affects Pieris brassicae L. host plant selection and orientation behaviour of a larval parasitoid - Bui, Thuy Nga T.; Himanen, Sari J.; Holopainen, Jarmo K. (Springer and Business Media, 2021)
Environmentally acquired chemical camouflage is a phenomenon, where a plant growing close to a strong volatile organic compound (VOC) emitter will adsorb and re-emit the VOCs produced by the neighbouring plant. The re-emitted volatile bouquet may resemble more the VOC composition of the neighbour than plant’s own typical odour, and thus act as chemical camouflage against insect detection, potentially simultaneously providing associational resistance towards herbivory. We exposed a pest-sensitive horticultural crop, Brassica oleracea var. italica (broccoli) cv. Lucky, to the volatiles emitted by Rhododendron tomentosum [RT] twigs and assessed the host selection by ovipositing females and larval instars of the major caterpillar pest Pieris brassicae between RT-exposed and control plants. Potential impact of RT exposure on herbivore natural enemies was studied using behavioural tests with a parasitoid wasp Cotesia glomerata. P. brassicae females laid significantly less eggs and egg clusters were fewer on RT-exposed plants at both night-time (6 °C) and daytime (22 °C) temperatures. Larvae preferred leaves from control plants over RT-exposed plants at both temperatures. Preceding RT-exposure did not disturb orientation of parasitoid wasp Cotesia glomerata females towards B. oleracea plants damaged by its host P. brassicae. However, host-damaged control plants were favoured by the parasitoid over RT-exposed, host-damaged plants. Our results suggest that companion plant based chemical camouflage as a mechanism of pest suppression could be developed as an additional tool for the integrated pest management toolbox in agriculture.
Keywords: Plant–plant volatile cues; Semivolatiles; Passive volatile adsorption; Orientation behaviour; Indirect defence; Associational resistance